2021
DOI: 10.3389/fimmu.2021.646874
|View full text |Cite
|
Sign up to set email alerts
|

Robust Prediction of Immune Checkpoint Inhibition Therapy for Non-Small Cell Lung Cancer

Abstract: BackgroundThe development of immune checkpoint inhibitors (ICIs) is a revolutionary milestone in the field of immune-oncology. However, the low response rate is the major problem of ICI treatment. The recent studies showed that response rate to single-agent programmed cell death protein 1 (PD-1)/programmed cell death-ligand 1 (PD-L1) inhibition in unselected non-small cell lung cancer (NSCLC) patients is 25% so that researchers defined several biomarkers to predict the response of immunotherapy in ICIs treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This hypothesis may also explain another finding in our study that RAD51AP1 expression was positively correlated with TMB in various tumors ( Figure 11B ). Moreover, TMB and MATH are effective biomarkers of immune checkpoint inhibitors (ICIs) treatment, and their increment in the tumor may indicate better ICIs therapy efficacy ( Gao et al, 2020 ; Jiang et al, 2021 ). Interestingly, we also found that cancer with higher RAD51AP1 expression often presented higher MSI ( Figure 11A ), which is positively correlated to ICIs therapy efficacy in CRC and other cancers ( Dudley et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis may also explain another finding in our study that RAD51AP1 expression was positively correlated with TMB in various tumors ( Figure 11B ). Moreover, TMB and MATH are effective biomarkers of immune checkpoint inhibitors (ICIs) treatment, and their increment in the tumor may indicate better ICIs therapy efficacy ( Gao et al, 2020 ; Jiang et al, 2021 ). Interestingly, we also found that cancer with higher RAD51AP1 expression often presented higher MSI ( Figure 11A ), which is positively correlated to ICIs therapy efficacy in CRC and other cancers ( Dudley et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited impact of current single-plexed PD assays and the complexity of tumour cell-host immunity interactions, bioinformatic models which integrate different tissue-, blood-and imaging-PD results may be needed to overcome the performance of single analytes and improve dose-finding strategies for specific IO agents [29]. Recent studies utilising an integrated biomarker approach to predict tumour response to IO agents have demonstrated improved performance over single independent biomarkers [30,31]. The future of PD analyses will likely rely on the joint use of different PD biomarkers depending on the expected biologic activity of the IO agent.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior attempts to predict immunotherapy responses have used ML-based approaches [14][15][16] , which are complex "black-box" systems that cannot handle missing data. As input, they require all of the necessary clinical and molecular information to be provided.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, machine learning (ML)-based methods have been applied to unravel the factors determining the efficacy of ICI treatment for NSCLC. For one example, the AUC of a neural network model that integrated several factors (TMB, PD-L1 score, mutant-allele tumor heterogeneity, and immune-related pathways) was as high as 0.80 in a test cohort 14 . Another study integrated PD-L1 score and CT images achieved an AUC of 0.76 15 .…”
Section: Introductionmentioning
confidence: 99%